On the Synchronisation of Elections – A differential Games Approach - António Caleiro (Universidade de Évora, Departamento de Economia, 2006)
The paper offers an analysis of the issues related to the election dates synchronisation between two countries. The first purpose of the paper is to analyse the circumstances in which a government of a single country, considered to be a small economy, has incentives, or not, to synchronise the domestic election dates with the election dates (not necessarily determined in an endogenous way) of a country performing the role of an `anchor', considered to be a big economy. To achieve this purpose, the paper uses an asymmetric version of MILLER and SALMON's (1990) model in order to derive the optimal domestic electoral period length, which, in this sense, can be said to be endogenously determined. The second main purpose of the paper is to re-analyse the situation being studied by considering that the foreign government also determines its election dates in an optimal way, this leading to a differential game played by the two incumbents from which incentives to totally synchronise the election dates may result. The paper shows that the interests of both economies in what concerns the existing electoral period length in the other economy are not always compatible.
Keywords: C73; E32; E61; F42; 330; Differential Games; Electoral Business Cycles; Election Dates; Mandates Duration; Synchronisation of Elections